CHARACTERIZING PROTEIN ARGININE METHYLTRANSFERASE EXPRESSION AND ACTIVITY DURING MYOGENESIS - Shen, Nicole (My University, 2017)
Despite the emerging importance of protein arginine methyltransferases (PRMTs) in regulating skeletal muscle plasticity, the biology of these enzymes during muscle development remains poorly understood. Therefore, our purpose was to investigate PRMT1, -4, and -5 expression and function in skeletal muscle cells during the phenotypic remodeling elicited by myogenesis. C2C12 muscle cell maturation, assessed during the myoblast stage, and during days 1, 3, 5, and 7 of differentiation, was employed as an in vitro model of myogenesis. We observed PRMT-specific patterns of expression and activity during myogenesis. PRMT4 and -5 gene expression was unchanged, while PRMT1 mRNA and protein content were significantly induced. Cellular monomethylarginines and symmetric dimethylarginines, indicative of global and type II PRMT activities, respectively, remained steady during development, while type I PRMT activity indicator asymmetric dimethylarginines increased through myogenesis. Histone 4 arginine 3 (H4R3) and H3R17 contents were elevated coincident with the myonuclear accumulation of PRMT1 and -4. Collectively, this suggests that PRMTs are methyl donors throughout myogenesis and demonstrate specificity for their protein targets. Cells were then treated with TC-E 5003 (TC-E), a selective inhibitor of PRMT1 in order to specifically examine the enzymes role during myogenic differentiation. TC-E treated cells exhibited decrements in muscle differentiation, which were consistent with attenuated mitochondrial biogenesis and respiratory function. In summary, this study increases our understanding of PRMT1, -4, and -5 biology during the plasticity of skeletal muscle development. Our results provide evidence for a role of PRMT1, via a mitochondrially-mediated mechanism, in driving the muscle differentiation program.
CHARACTERIZING PRMT BIOLOGY DURING MYOGENESIS
Keywords: Protein arginine methyltransferase; skeletal muscle; myogenesis; PGC-1α; mitochondria